A COMPARATIVE STUDY OF DEMOGRAPHIC AND SOCIO-ECONOMIC PROFILES OF RURAL AND URBAN ONLINE CONSUMERS OF HARYANA - Ms. Sucheta (International Journal of Multidisciplinary Research and Studies, 2023)
Traditionally, buying and selling had to be done in person between the seller and the buyer, but now both may be done virtually or online. E-commerce and E-marketing have become increasingly important concepts as information technology has grown, making internet purchases incredibly prevalent. So, a comparative study of demographic and socio-economic profiles of rural and urban online consumers of Haryana is decided. In this study sample of 600 people that shop online from rural and urban areas of Haryana were considered on the basis of their “geographical area and literacy rate”. The categories that are covered in the demographic profile are gender, marital status, and age of consumer but education, occupation, size of family, nature of family, income, and number of earning members are dealt with in the socio-economic profile of the study. For analyzing the data, descriptive statistics and frequency distribution tools are used. It is found that engagement in online shopping is seen more in males of rural areas in comparison to females. On other hand, urban females are more engaged in online shopping in comparison to males. The majority of online consumers from urban and rural areas are students having Professional degrees and diplomas respectively, unmarried age 16-34, and living in nuclear families. Earning, the number of earning members, and the tendency to spend are more in the families of urban consumers than rural consumers. Therefore, the study concludes that in the state of Haryana, most of the online consumers are youngsters and the consumers of urban areas are more engaged in online shopping in comparison to the people who are living in rural areas of the state.